2021
DOI: 10.1016/j.tcb.2021.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitylation at Stressed Replication Forks: Mechanisms and Functions

Abstract: Accurate duplication of chromosomal DNA is vital for faithful transmission of the genome during cell division. However, DNA replication integrity is frequently challenged by genotoxic insults that compromise the progression and stability of replication forks, posing a threat to genome stability. It is becoming clear that the organization of the replisome displays remarkable flexibility in responding to and overcoming a wide spectrum of fork-stalling insults, and that these transactions are dynamically orchestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 117 publications
0
17
0
Order By: Relevance
“…We also investigated the influence of HSP90B1 activity inhibition on MCM7 ubiquitylation. Immunoblotting analysis revealed that MCM7 proteins, which were enriched by immunoprecipitation through MCM7 antibody, underwent K48- and K63-ubiquitylation after HU treatment and the modification level increased with the stress intensity 41, 42 . Strikingly, inhibition of HSP90B1 activity with either inhibitor sharply increased both types of ubiquitylation levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We also investigated the influence of HSP90B1 activity inhibition on MCM7 ubiquitylation. Immunoblotting analysis revealed that MCM7 proteins, which were enriched by immunoprecipitation through MCM7 antibody, underwent K48- and K63-ubiquitylation after HU treatment and the modification level increased with the stress intensity 41, 42 . Strikingly, inhibition of HSP90B1 activity with either inhibitor sharply increased both types of ubiquitylation levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A phosphorylation-dependent SUMO modification (PDSM) motif, composed of a SUMO consensus site and an adjacent proline-directed phosphorylation site (ΚKxExxSP), promotes SUMOylation is apparent in several regulators of gene expression, including heat shock factors (HSFs) and TFs ( Hietakangas et al, 2006 ). In contrast to ubiquitylation, a modification with many known functions ( Dittmar and Winklhofer, 2019 ; Deng et al, 2020 ; Zhu et al, 2020 ; Mirsanaye et al, 2021 ), the substantially greater number of SUMOylated TFs highlight the importance of SUMOylation for modulating DNA transcription. SUMOylation modulates the function of TFs through multiple mechanisms, including interaction with histone deacetylase complexes and other transcriptional coregulators, inhibition of acetylation and phosphorylation, as well as availability to bind chromatin ( Rosonina et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, this complex molecule protects both fork integrity and promotes resistance of BRCA-deficient cells to PARP inhibitors. Based on this knowledge, it has been suggested that ubiquitinated PCNA may even operate parallel to the BRCA-RAD51 pathway to protect the replication fork progression [ 88 ]. Further experimental evidence made clear that, in response to DNA replication stress, the fork may reverse its direction thus providing time to start the repair procedure and preventing double-strand breaks [ 89 ].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%